P234 Transcutaneous CO2 measurement is not a reliable alternative to arterial blood gas sampling in the acute medical setting. (December 2018) - Mummery, V; Rodgers, E; Padmanaban, V; Matthews, D; Woodcock, T; Bloch, S
Abstract : Introduction: Measurement of pC02 in arterial blood is essential in the management of many unwell patients, especially those with respiratory failure. The gold standard method of measuring PaC02 is by arterial blood gas (ABG) sampling, which is painful, invasive, has potential complications, and can only be completed by those with skills to do so. ABG samples often need to be repeated several times in order to assess how a patient is responding to treatment over time. An alternative to repeat ABG sampling is inserting an arterial line, which is also painful, has potential complications, and requires high level nursing care. Transcutaneous pCO2 (TcCO2) monitoring potentially offers a non-invasive means of determining pCO2, and requires little skill to carry out. We hypothesised that TcCO2 can be used as an alternative to ABG sampling in the acute clinical setting and in patients who have physiological disturbances. Method pCO2 levels were measured by a transcutaneous CO2 monitor (Resmed SenTec) at the same time as arterial blood sampling (arterial stab or arteria line), taken only at a time that was clinically indicated. 74 paired samples were taken from 50 patients acute medical patients, with a maximum of 4 paired samples for each participant. The reliability of the TcCO2 as an alternative was assessed using Bland Altman Analysis. Results: Bland Altman analysis suggested that the bias of the TcCO2 tended to be 0.16 (CI ±1.54) kPa lower than the pCO2 with 95% limits of agreement −1.67 to 1.35 kPa (figure 1). The mean arterial blood pressure, heart rate, temperature, and oxygen saturations did not affect how much the TcCO2 measurement differed from the pCO2. Where samples were taken from the same patient at consecutive time points in only 13 of these 24 samples did the pCO2 change in the same direction when measured by the two techniques. Conclusion: TcCO2 should not be used as an alternative to the ABG to monitor arterial CO2 levels in the acute setting, and cannot be reliably used to suggest a trend or direction of change in CO2 level. Further research is required to find an alternative to the ABG.